2005
DOI: 10.1093/hmg/ddi414
|View full text |Cite
|
Sign up to set email alerts
|

Dazl binds in vivo to specific transcripts and can regulate the pre-meiotic translation of Mvh in germ cells

Abstract: Gametogenesis is a complex process subject to strict controls at both levels of transcription and translation. Members of a family of conserved RNA-binding proteins encoded by the DAZ genes are required for the translational regulation of gene expression essential for this process. Although loss of DAZ family genes is associated with infertility in several organisms including humans, the identity of the transcripts regulated in vivo is unknown. Using a combination of immunoprecipitation and microarray analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
185
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(207 citation statements)
references
References 51 publications
21
185
1
Order By: Relevance
“…These findings confirm the previously established regulatory role of DAZL on the expression of SCP3 and VASA in our in vitro derived germ cell system. DAZL has been shown to interact with Mvh mRNA, stimulating its translation in germ cells by binding to a site within the 3¢ UTR of the Mvh transcript [28]. Germ cells derived from Dazl knockout mice contain lower levels of MVH (VASA) protein, suggesting that the RNAbinding activity of the DAZL protein mediates regulation of Mvh translation in vivo [28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings confirm the previously established regulatory role of DAZL on the expression of SCP3 and VASA in our in vitro derived germ cell system. DAZL has been shown to interact with Mvh mRNA, stimulating its translation in germ cells by binding to a site within the 3¢ UTR of the Mvh transcript [28]. Germ cells derived from Dazl knockout mice contain lower levels of MVH (VASA) protein, suggesting that the RNAbinding activity of the DAZL protein mediates regulation of Mvh translation in vivo [28].…”
Section: Discussionmentioning
confidence: 99%
“…DAZL has been shown to interact with Mvh mRNA, stimulating its translation in germ cells by binding to a site within the 3¢ UTR of the Mvh transcript [28]. Germ cells derived from Dazl knockout mice contain lower levels of MVH (VASA) protein, suggesting that the RNAbinding activity of the DAZL protein mediates regulation of Mvh translation in vivo [28]. A similar regulatory mechanism was also reported to control Scp3 expression, in which DAZL facilitates Scp3 translation by interacting with the 3¢UTR of the Scp3 transcript [17].…”
Section: Discussionmentioning
confidence: 99%
“…DAZL is suggested to positively regulate the translation of the mRNA it binds, including DDX4 mRNA. DDX4 is a part of chromatoid bodies where RNA can be stored; there the transcripts DDX4 binds can be regulated by its acetylation [3,6,7].…”
Section: Discussionmentioning
confidence: 99%
“…DAZ member proteins are stimulators of translation. The target mRNAs of DAZ family member DAZL, include MVH (mouse VASA homologue), another gene critical for spermatogenesis [2][3][4]157].…”
Section: Rna Regulation In the Male Germlinementioning
confidence: 99%
“…Strikingly, a number of gene transcripts in Table 1 appear to be DAZL-binding targets (Sycp3, Tex19, Mvh, Stk31, Tex14, Tuba3, and Fthl17). Furthermore, it has also been shown that DAZL stimulates translation of Mvh by binding to its 3 ¶ untranslated region (UTR) (Reynolds et al 2005).…”
Section: Post-transcriptional Regulation In Meiosismentioning
confidence: 99%